TP10.2.5Investigating the impact of early COVID-19 policies on Emergency Surgical service at a District General Hospital. (28th October 2021) - Lunt, Adam; Hanger, Joseph; Bush, Alex; Christopoulos, Petros; Munro, Alicia; Keatley, Ben
Abstract: Aims: On the 23rd March 2020, the UK introduced measures to curb the spread of coronavirus disease 19 (COVID-19). We aimed to investigate the impact of government and Royal College measures on the acute surgical take. Materials and Methods: Retrospective analysis was performed for patients referred to the acute surgical take between 2nd March 2020 and 5th April 2020. Data were analysed in two groups; 'pre-COVID measures' cohort (prior to 23rd March 2020) and 'post-COVID measures' cohort (on or after 23rd March 2020). Demographics, Early Warning Score (EWS) at referral, blood results, radiological investigations, antibiotic use, diagnosis, operative and outcome data were compared. Results: 465 patient referrals were included. Mean admissions per day reduced by 39.9% (p = 0.01) in the post-COVID measures' cohort compared with the pre-COVID measures cohort. Disease severity increased, with white cell count (WCC) increasing by 14% (p = 0.02) and C-reactive protein (CRP) by 34% (p = 0.04). Laparoscopic procedures decreased by 86.4% (p < 0.01). The proportion of admissions requiring operative management showed no significant change, with 26% in pre-COVID measures verse 23% in post- COVID measures (p = 0.91). Short term morbidity, mortality and length of stay outcomes also demonstrated no significant change. Conclusion: Fewer patients were referred following the implementation of government and Royal College guidance, however these patients demonstrated greater disease severity. Guidance likely modified patients help seeking behaviours and delayed presentation time. Surgeons demonstrated good compliance to Royal College guidance by reducing laparoscopic procedures, however operative management rates remained constant.